2015
DOI: 10.1371/journal.pone.0117520
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-Methylbutyrate (HMB) Normalizes Dexamethasone-Induced Autophagy-Lysosomal Pathway in Skeletal Muscle

Abstract: Dexamethasone-induced muscle atrophy is due to an increase in protein breakdown and a decrease in protein synthesis, associated with an over-stimulation of the autophagy-lysosomal pathway. These effects are mediated by alterations in IGF-1 and PI3K/Akt signaling. In this study, we have investigated the effects of β-Hydroxy-β-methylbutyrate (HMB) on the regulation of autophagy and proteosomal systems. Rats were treated during 21 days with dexamethasone as a model of muscle atrophy. Co-administration of HMB atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…However, to date, no animal or human studies of HMB supplementation in liver disease have been performed. Murine myotubes exposed to HMB (50 μM) and LPS ↓ protein degradation and caspase activation Russell and Tisdale 86 Murine myotubes exposed to HMB (50 μM) and dexamethasone ↓ protein degradation, ↓ expression of atrogin-1 and MuRF1, ↓ reduction of myotube size Aversa et al 87 Murine myotubes exposed to HMB (10 mM) and myostatin ↓ fibre atrophy Mobley et al 88 Rat L6 myotubes exposed to HMB (25 μM) and dexamethasone ↓ lysosomal proteolysis induced by dexamethasone Girón et al 89 PIF, proteolysis-inducing factor; LPS, lipopolysaccharides. Rats, dexamethasone and co-administration of HMB (320 mg/kg/day orally) for 21 days ↓ the loss of body weight, lean mass and reduction of fibre cross-sectional area Girón et al 89 Rats, co-administration of dexamethasone and HMB (150 or 600 mg/kg/day orally) for 5 days ↓ muscle loss and damage and reduction in grip strength, ↓ MuRF1 expression…”
Section: Cachexia and Effects Of Hmb Supplementationmentioning
confidence: 99%
“…However, to date, no animal or human studies of HMB supplementation in liver disease have been performed. Murine myotubes exposed to HMB (50 μM) and LPS ↓ protein degradation and caspase activation Russell and Tisdale 86 Murine myotubes exposed to HMB (50 μM) and dexamethasone ↓ protein degradation, ↓ expression of atrogin-1 and MuRF1, ↓ reduction of myotube size Aversa et al 87 Murine myotubes exposed to HMB (10 mM) and myostatin ↓ fibre atrophy Mobley et al 88 Rat L6 myotubes exposed to HMB (25 μM) and dexamethasone ↓ lysosomal proteolysis induced by dexamethasone Girón et al 89 PIF, proteolysis-inducing factor; LPS, lipopolysaccharides. Rats, dexamethasone and co-administration of HMB (320 mg/kg/day orally) for 21 days ↓ the loss of body weight, lean mass and reduction of fibre cross-sectional area Girón et al 89 Rats, co-administration of dexamethasone and HMB (150 or 600 mg/kg/day orally) for 5 days ↓ muscle loss and damage and reduction in grip strength, ↓ MuRF1 expression…”
Section: Cachexia and Effects Of Hmb Supplementationmentioning
confidence: 99%
“…The administration of HMB in combination with arginine and glutamine amino-acids to stage IV cancer patients, increased their body mass when compared to placebo [44]. Furthermore, HMB exerts protective effects against dexamethasone-induced atrophy by down-regulating the activated Akt/FoxO and MuRF1 levels which controls autophagy and ubiquitin dependent proteolytic systems [42,45]. HMB is also involved in the regulation of satellite cell proliferation probably through reduction of nuclear apoptosis [46].…”
Section: ˇ-Hydroxy-ˇ-methylbutyrate (Hmb)mentioning
confidence: 99%
“…Regarding the increase in the weight of the tibialis anterior muscle 21 days after injury, studies suggest that the maximum peak of the effect of HMB starts in the second week of supplementation, 14,21 yet the increase in muscle weight did not reflect on the increase in CSA of the muscle fibers in the groups evaluated.…”
Section: Discussionmentioning
confidence: 92%
“…The study by Girón et al 21 demonstrated that HMB supplementation for 28 days was able to protect the CSA of the gastrocnemius and soleus muscles in a dexamethasone-induced atrophy model of young rats, considering that the supplementation started in the week prior to the atrophy protocol. In addition, according to other authors, the effects of HMB proved effective in a 28-30 day protocol, with one prior week of supplementation, when immobilization procedures were performed along with corticosteroid administration.…”
Section: Discussionmentioning
confidence: 99%